Dynamic characteristic analysis of rotating blade with breathing crack. (1st August 2023) - Xiong, Qian; Guan, Hong; Ma, Hui; Wu, Zhiyuan; Guo, Xumin; Wang, Weiwei
Highlights: A new dynamic model of a rotating aero-engine blade with breathing crack is established. The dynamic responses of a cracked blade are analyzed through the vibration energy method. A new indicator is proposed to quantify the severity of the crack based on the energy responses. Abstract: Crack is one of the most common blade faults in the aero-engine blade, which may cause serious accidents. The dynamic characteristics of cracked blades have been studied extensively, but the modeling of rotating blades with the edge crack by the shell element theory is still relatively inadequate. To make up for this gap, a new nonlinear dynamic model of a rotating cracked blade considering the breathing effect is proposed by the in-house code of the shell element. The proposed model is verified by comparing vibration responses with those obtained from ANSYS contact elements. Besides, a new crack fault diagnosis indicator for the rotating cracked blade with the breathing effect is proposed based on the vibration energy method. The mechanism of the indicator is explained detailedly through a mass-spring model and mathematical expressions. Additionally, the effects of the crack depth, crack location and aerodynamic amplitude on the nonlinear vibration characteristics of the rotating cracked blade are analyzed based on energy responses. The results indicate that: the more severe the crack, the greater the difference between extremums in the energy response accordingly; the frequency components corresponding to the maximum amplitude are different in the spectrum cascades of the energy and displacement, and the amplitude change laws can be used as an effective method for fault diagnosis of the cracked blade. Furthermore, the research can provide theoretical guidance for the detection and diagnosis of rotating cracked blades.